2009
DOI: 10.1016/j.ijom.2009.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties and apparent density of human edentulous maxilla and mandible

Abstract: The aim of this study aim was to determine whether elastic properties and apparent density of bone differ in different anatomical regions of the maxilla and mandible. Additional analyses assessed how elastic properties and apparent density were related. Four pairs of edentulous maxilla and mandibles were retrieved from fresh human cadavers. Bone samples from four anatomical regions (maxillary anterior, maxillary posterior, mandibular anterior, mandibular posterior) were obtained. Elastic modulus (EM) and hardn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 23 publications
4
44
0
3
Order By: Relevance
“…Posterior maxilla is very important region for implant strategy for oral rehabilitation, the possibility to find an animal model with bone characteristic similar is very important for research field. Seong et al (1) calculate the elastic modulus of posterior human maxilla bone and found results that range from 13.1 to 16.4, results very similar that were found in the current study. Additionally, the turnover of the rabbit is 3 times lower than human, than other advantage is the lower time consuming for complex experiments (24).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Posterior maxilla is very important region for implant strategy for oral rehabilitation, the possibility to find an animal model with bone characteristic similar is very important for research field. Seong et al (1) calculate the elastic modulus of posterior human maxilla bone and found results that range from 13.1 to 16.4, results very similar that were found in the current study. Additionally, the turnover of the rabbit is 3 times lower than human, than other advantage is the lower time consuming for complex experiments (24).…”
Section: Discussionsupporting
confidence: 89%
“…The primary function of the stomatognathic system is preparation and processing of food through a biomechanical process of biting and chewing (1,2). This mechanism is based on the transfer of masticatory forces, mediated through the implant or intact and restored teeth.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional Knoop microhardness test generally produces a large indentation (indentation length equivalent to a width of 5-20 enamel prisms) and is also influenced by the substrate 21) . Recent advances in the nanoindentation test allow the measurement of mechanical properties for extremely small volumes of material, and both the hardness and the elastic modulus can be determined simultaneously [22][23][24][25] . However, microradiography is a better analysis method if it is important to know mineral content profiles, because a previous research 28) reported that there was a moderate linear relationship (R 2 =0.81) between mineral content and the square root of hardness by nanoindentation testing.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional Knoop microhardness test generally produces a large indentation (indentation length equivalent to a width of 5-20 enamel prisms) and is also influenced by the substrate 23) . However, recent advances in nanoindentation tests now allow the measurement of mechanical properties of extremely small volumes of material, and the hardness and elastic modulus can be determined simultaneously [25][26][27][28][29] . In the present study, a depth-dependent analysis of the enamel surface region was performed with an isotropic voxel size of 3.6 µm in µCT scanning images and with a 5-µm interval for indentations in nanoindentation testing.…”
Section: Discussionmentioning
confidence: 99%